Enhancement by Ticlopidine of the Inhibitory Effect on In Vitro Platelet Aggregation of the Glycoprotein IIb/IIIa Inhibitor Tirofiban - Umemura, K; Kondo, K; Ikeda, Y; Nakashima, M (Thrombosis and Haemostasis, 1997)
We determined the effects of combining the glycoprotein IIb/IIIa inhibitor tirofiban (MK-383, Aggrastat) and ticlopidine on inhibition of ADP-induced platelet aggregation, inhibition of collagen-induced platelet aggregation, and prolongation of bleeding time in 5 healthy male volunteers. The study consisted of 2 periods. In period 1, tirofiban was administered intravenously as a bolus injection at a dose of 5.0 µg/kg for 5 min, then as a continuous infusion at a rate of 0.05 µg/kg/min for 5 h 55 min. In period 2, ticlopidine was given orally at a dose of 200 mg once daily for 4 days, after which tirofiban was administered in the same manner as in period 1, starting 2 h after the last dose of ticlopidine. The percent inhibition of platelet aggregation induced by ADP 5 µM at the end of tirofiban infusion in periods 1 and 2 was 73.6 ± 2.6 and 87.1 ± 5.7% (mean ± SD), respectively. The corresponding values for inhibition of platelet aggregation induced by collagen 2 µg/ml were 45.4 ± 36.1 and 82.8 ± 27.0%, respectively. In contrast, the percent inhibition of platelet aggregation induced by ADP and collagen after treatment with ticlopidine alone was 15.8 ± 20.2 and p ± 4.8%, respectively. Compared with tirofiban alone, the combination of tirofiban and ticlopidine significantly enhanced inhibition of platelet aggregation induced by both ADP and collagen (p <0.02 and p <0.012, respectively). The inhibitory effects of ticlopidine alone were not statistically significant. Tirofiban prolonged bleeding time both in period 1 and in period 2. However, tirofiban and ticlopidine combined did not affect bleeding time. Ticlopidine administration did not alter the pharmacokinetics of tirofiban. In conclusion, at the doses of tirofiban and ticlopidine used in this study, the combination of the two drugs enhanced inhibition of platelet aggregation but did not prolong bleeding time, suggesting that appropriate doses of tirofiban can be used concomitantly with ticlopidine with no further safety concerns but with potential additional clinical effects.